Models of Hyperbole and Personification: Studies of the Al-Qur'an - Tika Mardiyah; Achmad Fudhaili (Al-Muyassar: Journal of Arabic Education, 2023)
This study aims to investigate the linguistic structure contained in Al-Qur’an. This research focuses on the Hyperbole and Personification style found in the verses of Al-Qur’an. The object of this research study is Al-Qur’an itself with the help of several references from similar studies. This study uses a text analysis method with a qualitative approach. This research reveals that there are many examples of hyperbole and personification in Al-Qur’an. The style of hyperbole in the science of Balaghah is called mubalaghoh. And the style of personification in the science of Balaghah is called isti'aroh makniyah. Several verses in Al-Qur’an that contain personification figures of speech, namely Q.S. Ali-Imran: 24, At-Takwīr (QS: 81: 17), Al-Fajr (QS: 89: 4), Asy-Syams (QS: 91: 2-4), Al-Lail (QS: 92), Al-Kauśar (QS: 108: 2) and so on. The style of Hyperbole or Mubalaghah in Al-Qur’an is found in surah an-Nur (24): 40, Al-A`raf (7): 40, and Q.S. Nur (24): 35.